SISTEM APLIKASI PEMBELAJARAN JUZ ‘AMMA MENGGUNAKAN WEB MOBILE UNTUK MENINGKATKAN MINAT HAFALAN SURAT PENDEK SISWA MI MIFTAHUL HUDA SENDANG AGUNG - Andoyo, Andreas; Aji, Dwiki Wachyu; Mukodimah, Siti (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2019)
With the development of technology in the world that is increasingly sophisticated and makes it easier for humans in the world of work and others.Especially by using a smartphone one of the tools in the modern era that cannot be separated from human hands, smartphones can also be a tool to memorize Juz Amma more easily. Parents will also support if the smartphone is used for positive activities and parents do not feel worried that their child is wrong to use negative activities. The results of the research using the Inventor app which is in the form of the Juz Amma application.